Pengaruh Earning Per Share Dan Bi-7 Day Reverse Repo Rate Terhadap Harga Saham PT Bank Tabungan Negara (Persero) Tbk Periode 2016-2020 - Sovi Siti Sri Mulyani; Jujun Jamaludin; Badriyatul Huda (Jurnal Dimamu, 2021)
This study aims to find out how the effect of EPS on the stock price at PT BTN (Persero) Tbk, knowing how the influence of BI7DRR on the stock price at PT BTN (Persero) Tbk, and knowing how the influence of EPS and BI7DRR on the stock price at PT BTN (Persero). Tbk. The objects of research in this report are EPS, BI7DRR, and the share price of PT BTN (Persero) Tbk. The type of research is quantitative associative, the type of data is secondary data and uses data collection techniques in the form of documentation and literature study. While the sampling technique is purposive sampling, with a population of all financial statements of PT BTN (Persero) Tbk and BI7DRR with a sample of quarterly data for the financial statements of PT BTN (Persero), Tbk and BI7DRR for the 2016-2020 period. The results showed that there was a positive influence between EPS on stock prices at PT BTN (Persero), Tbk with the results of the tcount > ttable (1.7450 > 1.734) with a coefficient of determination of 0.1415, and there was no influence between BI7DRR on the price. Shares in PT BTN, Tbk with the results of the t-test < ttable (0.0880 < 1.734) with a coefficient of determination of 0.0077, and simultaneously there is no effect between EPS and BI7DRR on the stock price at PT BTN, Tbk with the results of the f-test < ftable (1.5202 < 3.59) with a coefficient of determination of 0.1519.